Spearman's hypothesis not supported? Three meta-analyses of Black and White prisoners, Northeast Asians, and Arabs and Jews. (15th October 2017) - te Nijenhuis, Jan; van den Hoek, Michael; Metzen, Daniel; David, Hanna
Abstract: Spearman's hypothesis states that differences between groups on the subtests of an IQ battery are a function of the g loadings of these subtests, and it is virtually always supported. There are anomalies: comparisons for which Spearman's hypothesis shows no supporting evidence. What they all have in common is an unusual Verbal/Performance profile. We carried out meta-analyses for these comparisons: Black and White prisoners, Asians and Whites, and Arabs and Jews in Israel. We carried out three meta-analyses based on, respectively, 2 data points and a total N = 575; 15 data points and a total N = 8100; 5 data points and a total N = 730. In all three meta-analyses Spearman's hypothesis showed no supporting evidence with sample-size weighted correlations with values of, respectively, −.18, .01 and −.24. Correcting for reliability led to similar outcomes. Bypassing the unusual V/P profile by testing Spearman's hypothesis separately on Verbal subtests and Performance subtests led to a confirmation in approximately half of the comparisons. So, it could be that the unusual V/P profile obstructs support for Spearman's hypothesis in approximately half of the cases. We conclude that the anomalies appear to be more in line with Spearman's hypothesis than previously thought. Highlights: Spearman's hypothesis: group differences are a function of g -loadedness of subtests. Spearman's hypothesis is tested on prisoners, Northeast Asians, and Jews and Arabs. Three meta-analyses do not support Spearman's hypothesis. Spearman's hypothesis appears to be supported half of the time at level of scales.